Bacterial Community with Plant Growth-Promoting Potential Associated to Pioneer Plants from an Active Mexican Volcanic Complex - Clara Ivette Rincón-Molina; Esperanza Martínez-Romero; José Luis Aguirre-Noyola; Luis Alberto Manzano-Gómez; Adalberto Zenteno-Rojas; Marco Antonio Rogel; Francisco Alexander Rincón-Molina; Víctor Manuel Ruíz-Valdiviezo; Reiner Rincón-Rosales (Microorganisms, 2022)
Microorganisms in extreme volcanic environments play an important role in the development of plants on newly exposed substrates. In this work, we studied the structure and diversity of a bacterial community associated to Andropogon glomeratus and Cheilanthes aemula at El Chichón volcano. The genetic diversity of the strains was revealed by genomic fingerprints and by 16S rDNA gene sequencing. Furthermore, a metagenomic analysis of the rhizosphere samples was carried out for pioneer plants growing inside and outside the volcano. Multifunctional biochemical tests and plant inoculation assays were evaluated to determine their potential as plant growth-promoting bacteria (PGPB). Through metagenomic analysis, a total of 33 bacterial phyla were identified from A. glomeratus and C. aemula rhizosphere samples collected inside the volcano, and outside the volcano 23 bacterial phyla were identified. For both rhizosphere samples, proteobacteria was the most abundant phylum. With a cultivable approach, 174 bacterial strains were isolated from the rhizosphere and tissue of plants growing outside the volcanic complex. Isolates were classified within the genera Acinetobacter, Arthrobacter, Bacillus, Burkholderia, Cupriavidus, Enterobacter, Klebsiella, Lysinibacillus, Pantoea, Pseudomonas, Serratia, Stenotrophomonas and Pandoraea. The evaluated strains were able to produce indole compounds, solubilize phosphate, synthesize siderophores, showed ACC deaminase and nitrogenase activity, and they had a positive effect on the growth and development of Capsicum chinense. The wide diversity of bacteria associated to pioneer plants at El Chichón volcano with PGPB qualities represent an alternative for the recovery of eroded environments, and they can be used efficiently as biofertilizers for agricultural crops growing under adverse conditions.